Analisis Kelayakan Investasi Pengembangan Sistem Penyediaan Air Minum IKK Patumbak di Kabupaten Deli Serdang (Studi Kasus) - Tania Nazria Purba; Ahmad Perwira Mulia Tarigan; Gina Cyntia R. Hasibuan (Syntax Corporation Indonesia, 2023)
This study is motivated by the actual conditions for the drinking water supply system in Patumbak District which has been served by PDAM Tirta Deli as the manager of drinking water in Deli Serdang Regency, and partially served by PDAM Tirtanadi, but the service coverage is still low at 30.33%. The purpose of this research is to study the Feasibility of Economic and Financial Investment in the development of drinking water supply systems. The data processing technique in this study is to use a monte carlo simulation technique. This Monte Carlo simulation is run through an application program, namely the R Studio program which will estimate the profit of a SPAM company for the next 20 years.. Based on the results of calculations and analysis, it can be concluded that from the analysis of economic and financial aspects the results are: NPV IDR 12,659,105,099 (> 0), IRR 14.58% (> 12%), Net B/C Ratio 2.796 (> 1). Results The average NPV value based on the Monte Carlo simulation results with R Studio is IDR 1,060,115,259 and from the analysis of the financial aspects the results are: The NPV value is IDR 25,994,551 (> 0), IRR 9.48 % (> 9.20 %) , Net B/C Ratio 1.03 (> 1), PP 9th year, BEP 0. So it can be concluded that SPAM Development Investment IKK Patumbak in Deli Serdang Regency is said to be FEATURED economically and financially.